Structural and interaction studies of the NS4B integral membrane protein from dengue virus - Lee, Le Tian (2017)
Dengue Virus (DENV) is a member from the Flavivirus genus of positive-stranded RNA (+RNA) viruses, which includes several other major human pathogenic viruses. Disease manifestation of DENV infection ranges from a self-limiting dengue fever (DF) to life threatening forms - dengue haemorrhagic fever (DHF) or dengue shock syndrome (DSS). Due to a combination of urbanisation, globalisation, and climate change over the recent decades, DENV has emerged as the major arbovirus causing diseases in the world. It is now estimated that 40% of the world population is at risk of dengue. However, there is currently no drug available for dengue treatment, and the approved Dengvaxia vaccine has only approximately 60% efficacy. Therefore, there is an urgent need to develop effective anti-dengue therapies. Unfortunately, drug discovery is hampered by the need to target all four serotypes simultaneously, as well as by our still relatively poor understanding of dengue disease progression and pathogenesis. Non-structural protein (NS) 4B from DENV is an essential player during viral replication, and has been identified by several groups as a potential target for drug development. However, its intrinsic membrane association and non-enzymatic nature has impeded progress in our understanding of NS4B. In this project, we aimed to better understand the biological roles of NS4B and also to assist drug development of anti-dengue compound through inhibition of NS4B activities. This goal was approached using three strategies, 1) to overexpress and crystallise NS4B for structural determination; 2) to map the NS4B-NS3 interaction; and 3) to identify new host factors interacting with NS4B during viral replication. Structural determination of NS4B - various recombinant NS4B protein constructs were successfully expressed, purified to monodispersity and the yield were sufficient for crystallisation studies. Crystals were obtained using vapour diffusion, antibody-assisted crystallisation and lipidic cubic phase (LCP) methods. However, most of the crystals were not reproducible or did not diffract. Only a few crystals produced weak diffractions, but were not sufficient for solving the NS4B structure. Structural determination by coupling cryo-electron microscopy (cryo-EM) with NS4B purified using styrene maleic acid (SMA) is the most promising technique at the moment, but more experiment to optimise sample preparation for cryo-EM is needed. Mapping NS4B-NS3 interaction - the NS4B-NS3 interaction was mapped using a combination of biochemical, biophysical and genetic approaches. We mapped the interaction to subdomains 2 and 3 of NS3 helicase (NS3hel) and the cytoplasmic loop of NS4B. 12 residues on the NS4B cytoplasmic loop putatively involved in mediating the interaction were identified, and further genetic analysis using alanine substitutions, demonstrated that Q134, G140 and N144 are important for DENV replication, possibly due to their involvement in interacting with NS3hel. Q134 was subsequently confirmed by other authors to be involved in mediating NS4B-NS3 interaction. Co-crystallisation of NS3hel domain with synthesised NS4B cytoplasmic loops was explored, but only apo-NS3hel crystals were obtained. Identify new host factors interacting with NS4B - we identified 106 host proteins that interact with NS4B during DENV replication using a novel approach of coupling quantitative stable isotope labeling with amino acids in cell culture mass spectrometry (SILAC MS/MS) with immunoprecipitation (IP). Subsequent short interfering RNA (siRNA) validation experiments identified Sec61α as an important host factor for DENV replication, and biochemical validation demonstrated the association of Sec61α with NS4B during viral replication. Finally, we demonstrated that inhibition of the Sec61 translocation complex (to which Sec61α is a component of) using a natural product, decatransin, led to potent inhibition of DENV replication. In summary, our results provide important materials for further studies of NS4B, including inhibitor design.